Resultado fiscal estrutural: desafios para uma nova meta orçamentária nacional - Pinto, Vilma da Conceição (2018)
The objective of this work is to estimate the primary structural fiscal budget for Brazil, adapting the methodology proposed by the Economic Policy Secretariat (SPE), in order to validate if the indicator is robust enough to be able to make a fiscal rule (the structural fiscal primary goal). The adaptations aim to bring greater transparency to the calculation of the structural fiscal budget indicator, in addition to explaining a methodological problem that may weaken the indicator. Thus, this study found that some fiscal data, necessary for the decomposition of revenues into clusters, did not come from public sources of information, and it is necessary to adapt the distribution of revenues to calculate the elasticities. It was also found that depending on the potential product methodology used to calculate the indicator, it can completely change its result, generating very different interpretations. Therefore, the study warns of the urgent need for a more robust potential product methodology, as well as more transparent information, so that the debate about the possibility of having a fiscal rule aimed at the structural fiscal result indicator is initiated.